1989
DOI: 10.1159/000200103
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole in the Short-Term Treatment of Reflux Oesophagitis

Abstract: Studies with short-term administration of omeprazole in patients with erosive or ulcerative reflux oesophagitis have demonstrated that strong inhibition of gastric acid secretion will become the therapy of choice for these patients. However, because reflux oesophagitis relapses rapidly when short-term treatment is discontinued, these patients are candidates for maintenance treatment. In most cases, long-term treatment will also require strong inhibition of gastric acidity. Until more information on the long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…PPIs are effective in the treatment of many gastrointestinal disorders including peptic ulcers, gastroesophageal reflux disease, Zollinger-Ellison syndrome and Helicobacter pylori infection (3)(4)(5)(6). PPIs should be used as first-line agents in the treatment of Zollinger-Ellison syndrome (4,7-10) and moderate to severe reflux esophagitis that is confirmed by endoscopy (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). To eradicate H pylori, the use of PPIs in combination with one or more of the following antibiotics for either seven (22)(23)(24) or 14 (25,26) days of therapy has been suggested: amoxicillin, clarithromycin, metronidazole and tetracycline.…”
Section: Pertinence Des Prescriptions D'oméprazole Chez Les Personnesmentioning
confidence: 99%
“…PPIs are effective in the treatment of many gastrointestinal disorders including peptic ulcers, gastroesophageal reflux disease, Zollinger-Ellison syndrome and Helicobacter pylori infection (3)(4)(5)(6). PPIs should be used as first-line agents in the treatment of Zollinger-Ellison syndrome (4,7-10) and moderate to severe reflux esophagitis that is confirmed by endoscopy (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). To eradicate H pylori, the use of PPIs in combination with one or more of the following antibiotics for either seven (22)(23)(24) or 14 (25,26) days of therapy has been suggested: amoxicillin, clarithromycin, metronidazole and tetracycline.…”
Section: Pertinence Des Prescriptions D'oméprazole Chez Les Personnesmentioning
confidence: 99%
“…The significance of pronounced acid inhi bition for the treatment of reflux oesophagi tis has not been settled by studies using his tamine H2-receptor antagonists [15][16][17], In fact, the efficacy of histamine H2-reccptor antagonists in healing of erosive or ulcer ative reflux oesophagitis is disappointing. After treatment with 300 or 400 mg q.i.d.…”
Section: 11]mentioning
confidence: 99%
“…Surprisingly, no studies using high doses of H2-receptor antagonists have been reported in patients with reflux oe sophagitis. Interestingly, recent studies using high and very high doses of up to 1,800 mg ranitidine daily have shown that these in creased doses significantly raise intra-oesophageal pH in patients with ulcerative re flux oesophagitis when compared with the recommended lower doses of the drug [17,18]. In the absence of controlled clinical studies on healing of reflux oesophagitis with such high dose of H2-receptor antagonists, other therapeutic options have been ex plored, such as the mucosa-protecting agent sucralfate, the prokinetic drug cisapride and combinations of various modalities [15,17], However, these approaches have not been proven to be superior to treatment with H2-receptor antagonists.…”
Section: 11]mentioning
confidence: 99%